Integrating Resource Management and Timeline-Based Planning - Umbrico, Alessandro; Cesta, Amedeo; Cialdea Mayer, Marta; Orlandini, Andrea (Proceedings of the International Conference on Automated Planning and Scheduling, 2018)
This paper describes how explicit resource reasoning is added within an existing temporal planning framework that uses timelines as plan representation. The work is grounded on a recent formalization of timeline-based planning that here is extended to model and reason over resources. The formal account is then fully implemented as an extension of the PLATINUm planner and tested to demonstrate its new capabilities.